The simplified expression are as follows;
6mn³ - mn² + 3mn³ + 15mn² = 9mn³ + 14mn²
a⁴b³ + 8a⁴b³ = 9a⁴b³
<h3>How to simplify an expression?</h3>
A simplified expression is express to its lowest term.
Therefore,
6mn³ - mn² + 3mn³ + 15mn²
combine like terms
6mn³ + 3mn³ - mn² + 15mn²
9mn³ + 14mn²
a⁴b³ + 8a⁴b³ = 9a⁴b³
learn more on simplification here: brainly.com/question/403991
#SPJ1
Step-by-step explanation:
7+5(x) ( between here write the greater than or equal to sign) -9
Answer:
7 feet
Step-by-step explanation:
Pythagorean theorem
sqrt(4.5^2 + 5.3^2) = hypotenuse
sqrt(48.34) = hypotenuse
6.95269732 = hypotenuse
round to nearest tenth
7 feet = the length of the hypotenuse
Answer:
81°
Step-by-step explanation:
Please refer to the attachment(s) for explanations